2021
DOI: 10.1002/cnr2.1464
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab plus bevacizumab treatment for unresectable hepatocellular carcinoma: Early clinical experience

Abstract: Background: Although atezolizumab plus bevacizumab (Atez/bev) treatment has been developed for unresectable hepatocellular carcinoma (u-HCC), changes in hepatic function during therapy have yet to be reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
42
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 45 publications
(67 reference statements)
12
42
2
Order By: Relevance
“…On the other hand, some reports on the initial experience of Atezo + Bev in real-world practice have already been reported. According to these reports, the efficacy was similar in patients who were initiated as first-line treatment and in patients who had a history of prior systemic treatment [14][15][16]. However, in our study, the ORR decreased slightly in the second-line or later treatment group, so this finding also needs further investigation.…”
Section: Discussionsupporting
confidence: 42%
“…On the other hand, some reports on the initial experience of Atezo + Bev in real-world practice have already been reported. According to these reports, the efficacy was similar in patients who were initiated as first-line treatment and in patients who had a history of prior systemic treatment [14][15][16]. However, in our study, the ORR decreased slightly in the second-line or later treatment group, so this finding also needs further investigation.…”
Section: Discussionsupporting
confidence: 42%
“…Several real-world clinical studies have shown that Atezo/Bev therapy has comparable safety profiles and efficacy, as observed in the IMbrave150 study [4,5]. However, the objective response rate (ORR) and disease control rate (DCR) reported for Atezo/Bev in the updated analysis of the IMbrave150 trial are 29.8% and 73.9%, respectively [6].…”
Section: Introductionmentioning
confidence: 94%
“…10 The therapeutic potential of ATZ + BV for u-HCC in clinical practice has also been reported in several very recent studies. [11][12][13][14][15] However, since HCC patients with a history of MTA therapy and those with Child-Pugh B cirrhosis were excluded in the IMbrave150 trial, the recent reports about the safety and efficacy of ATZ + BV in these patients are not adequate. In real-world clinical practice, the combination therapy is used not only for MTA-naïve cases, but also as second-or third-line treatment in MTA-experienced cases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, strictly speaking, there was a difference in the patient population between our study and Sho et al's report, which could have led to the observed difference in the therapeutic effect. Additionally, since some reports have shown that the effect of ATZ + BV does not differ depending on the patient's history of MTA,[11][12][13] while other reports have shown a difference,14,26,27 no consensus about this seems to have been reached as yet. Regarding the difference in treatment results of ATZ + BV as a later line therapy, it seems that the effect of ATZ + BV treatment also differs depending on whether the previous treatment was withdrawn due to AEs or PD.…”
mentioning
confidence: 99%